PREPARATION OF Ni-Mo/MORDENITE CATALYSTS UNDER THE VARIATION OF Mo/Ni RATIO AND THEIR CHARACTERIZATIONS FOR STEARIC ACID CONVERSION - Wega Trisunaryanti; Triyono Triyono; Denty Fibirna A (Indonesian Journal of Chemistry, 2003)
The preparation of Ni-Mo/Mordenite catalysts with variation of Mo/Ni ratio and their characterizations for conversion of stearic acid have been conducted. The catalysts were prepared by loading a small amount of nickel and/or molybdenum on H-Mordenite (H-Mor) with total metal content = 1 wt% based on the mordenite. The metals was supported on to the mordenite by impregnation method using nickel nitrate and/or ammonium heptamolybdate solution. The Mo/Ni ratio was varied as follows 0/1, 1/0, 1/1, 2/1, and 3/1 produced Ni/Mor, Mo/Mor, Ni1-Mo1/Mor, Ni1-Mo2/Mor and Ni1-Mo3/Mor catalyst respectively. The catalysts were then calcinated with nitrogen, oxidized with oxygen and reduced by hydrogen.The characterizations of catalyst were carried out by measuring Ni and Mo contents using atomic absorbtion spectroscopy (AAS), acidity by ammonia vapour adsorption, specific surface area and pore size distribution by nitrogen gas adsorption (NOVA-1000). The catalyst characters on conversion of stearic acid were performed in a flow reaction system at 4000C under hydrogen stream (10 mL/min).The AAS analyses showed that the metal impregnated on to the H-Mor sample were consistent to the initial metal concentrations. The loading of Ni and/or Mo enhanced the acidity, however decreased the specific surface area and total pore volume of the H-Mor sample. The higher the acidity the higher the conversion of stearic acid and the lower the coke formation. The other catalyst characters gave the variation effects toward the stearic acid conversion. The conversions of stearic acid were 34,52%,  43,33%, 65,10%, 80,10%, 86,42% and 95,72% produced by Ni1-Mo3/Mor, H-Mor, Mo/Mor, Ni/Mor, Ni1-Mo2/Mor and Ni1-Mo1/Mor catalyst, respectively.